Ohranjanje, predstavitev in uporaba kulturne dediščine na primerih ljubiteljskega gledališča - Vrtovec Beno, Ana (Amfiteater (Ljubljana), 2020)
The article discusses different approaches and case studies of amateur theatrical activity from the Slovenian ethnic space which draw on the past and, by employ various theatrical techniques (such as the use of text and costumes), "revive it" on special occasions for the audience. The important segment of such theatrical events is the content the actors represent, as the emphasis is on presenting different (local) heritage, e.g., customs and traditions, crafts, important historical figures and past events. As these traditions are well-known and recognised by the local community, it is something shared between the actors and the audience. Thus, such performances are usually very popular. We will investigate how these traditions influence the selection of theatrical space, the time of the performance, costumes, props, articulation, gesticulation, etc.
Keywords: amateur theatre; dediščina; heritage; identiteta; identity; ljubiteljsko gledališče; performance; uprizoritev